ANALYSIS OF COMPLIANCE IN PREPARATION OF BLUD FINANCIAL REPORTS TOWARDS PERMENDAGRI NO. 79 OF 2018 CASE STUDY OF S. PARMAN PUBLIC HEALTH CENTER BANJARMASIN - Hikmahwati; Rizky Amelia; Tino Kemal Fattah; Julkawait (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the level of compliance with the preparation of financial statements at the S. Parman Banjarmasin Health Center based on Permendagri No. 79 of 2018. The object of the research is the financial statements for the fiscal year 2022, which consists of seven main components: LRA, SAL, Balance Sheet, Operational Statements, Cash Flows, Equity Changes, and CaLK. This study uses a descriptive qualitative approach with data collection techniques through interviews, documentation, and observation. The results of the study show that the S. Parman Health Center has prepared complete financial statements and according to the set format, using an accrual basis in accordance with SAP. All reports have been prepared in a timely manner and reflect compliance with budget allocations within the RBA. In addition, accounting policies are also implemented consistently. This reflects transparency and accountability in BLUD's financial governance. The SILPA value of IDR 98,981,526 in the SAL Report shows budget efficiency. Thus, it can be concluded that the S. Parman Health Center has fulfilled the provisions in Permendagri No. 79 of 2018, as well as showing professional and accountable public financial reporting practices.